Teachers' language use: directions and administration conversation in classroom interaction - Kisman Salija; Asmaul Husna; Jusmianti Garing (Center for Humanities and Innovation Studies, 2022)
The intuition that happens within the classroom exercises when instructors and understudies exchange their thoughts through communication illustrates its viability. Understudies can grow their verbal capabilities when they uncover more remote dialect input by hearing the teachers use the target language in classroom interaction and practicing it when they have openings to communicate utilizing English as the target dialect. The perception appeared that instructors used target dialect more for administration conversation than for directions conversation. This research applied descriptive qualitative research. Qualitative research design aims to describe the data in more detail in a broader sentence clarification. The members of this investigation were two English teachers from one Public Islamic Senior High School in Parepare City, South Sulawesi, Indonesia. This study found that all language functions occurred in teachers 1 and 2 teaching activities in the instructional talk. Teacher 1 used more management talk in the classroom about welcoming, checking nearness, giving instruction, empowering understudies, giving commendations, inquiring about an address, and closing action. In the classroom, it was found that all the teachers spoke all language functions in the class. By analyzing the extracts by teacher 1, there are five unspoken language functions. Teacher 2 extract showed that there are seven unspoken language functions. The teachers believed that using the students' native language was critical to their comprehension. They moreover accept that the utilization of target dialect was imperative in expanding students' comprehension.